Sheet metal molding materials and molded products
Patent Information
- Application Number
- JP2022517690
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-04-28
- Filing Date
- 2021-04-22
- Publication Date
- 2025-03-27
- Estimated Expiration
- 2041-04-22
Smart Images

Figure 0007652764000001 
Figure 0007652764000002 
Figure 0007652764000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a thin plate molding material and a molded article, and more particularly to a thin plate molding material and a molded article containing a cured product of the thin plate molding material. [Background technology]
[0002] Conventionally, molded articles made of molding materials containing unsaturated polyester resins (especially SMC (sheet molding compound)) have been used in various fields due to their excellent appearance, mechanical properties, water resistance, corrosion resistance, and the like.
[0003] As such a molding material, for example, a molding material containing an unsaturated polyester, a filler, and reinforcing fibers has been proposed (see, for example, Patent Document 1 below). [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2009-29921 A Summary of the Invention [Problem to be solved by the invention]
[0005] Such molding materials are sometimes used in automobile parts mainly for the purpose of weight reduction. Specifically, the density (reduction), mechanical properties (improvement), and plate thickness (thinning) of the molded product are important for weight reduction. In particular, thinning of plate thickness has become a major weight reduction method in recent years, as it can reduce the amount of raw material required for parts and achieve not only weight reduction (weight reduction) but also cost reduction and resource conservation. In addition, inner panels such as door stiffeners are required to use materials with low density and excellent mechanical properties, that is, molding materials with excellent specific strength and specific rigidity, in order to meet the strength and rigidity required for parts, and to reduce weight by realizing a high section modulus in a thin plate by complex cross-sectional shapes such as bead shapes, and molding materials are required to be moldable into thin plates with complex shapes.
[0006] However, for example, although the mechanical properties of the molding material are improved by increasing the amount of reinforcing fibers, in the case of glass fibers, which are commonly used as reinforcing fibers, the density increases and the weight reduction effect decreases, and reinforcing fibers generally reduce the fluidity of the molding material, making it difficult to mold it into a thin plate. In addition, to make the plate thinner, the molding material needs to have mechanical properties that allow it to obtain sufficient strength and rigidity even if the part is thin (in other words, in order to satisfy the strength and rigidity of the part, the plate can only be made thin according to the mechanical properties), and as mentioned above, simply increasing the reinforcing fibers causes a tradeoff between the thin plate formability and mechanical properties of the molding material.
[0007] In the molding material of Example 1 of the prior art, the total amount of components excluding the filler and reinforcing fibers (hereinafter referred to as resin components) is low at 48 volume %, and the content of reinforcing fibers is low at 20 volume %. Although such molding material can obtain a high degree of smoothness required for automobile exterior panels due to the relatively high proportion of filler, it has poor thin plate formability, and the formability (thin plate formability) for a mold that requires a thin plate (for example, a plate thickness of 1.5 mm) is reduced, and there are problems in that the specific strength and specific rigidity required to obtain the strength and rigidity of a part cannot be satisfied for a thin plate (for example, a plate thickness of 1.5 mm).
[0008] The object of the present invention is to provide a thin plate molding material that has excellent formability (thin plate formability) for a mold that requires a thin plate, and also has excellent specific strength and specific rigidity that allows the strength and rigidity of parts to be obtained even in a thin plate, and a molded product containing the cured product of the thin plate molding material. [Means for solving the problem]
[0009] The present invention [1] is a thin plate molding material comprising a resin composition containing a resin component and a filler, and reinforcing fibers having a fiber length of 10 mm or more and 60 mm or less, the content of the reinforcing fibers being 21 vol.% or more and 28 vol.% or less, and the blending ratio of the resin component being 49 vol.% or more and 56 vol.% or less.
[0010] The present invention [2] includes the thin plate molding material according to the above [1], in which the aspect ratio of the reinforcing fibers is 500 or more.
[0011] The present invention [3] includes the thin plate molding material according to the above [1] or [2], in which the filling material contains a filler having an average maximum length of 15 μm or more and 300 μm or less.
[0012] The present invention [4] includes the thin plate molding material according to the above [3], in which the filler is hollow glass having an average maximum length of 15 μm or more and 50 μm or less.
[0013] The present invention [5] includes the thin plate molding material according to the above [3], in which the filler is milled carbon fiber having an average maximum length of 100 μm or more and 300 μm or less.
[0014] The present invention [6] includes the thin plate molding material according to any one of the above [1] to [5], wherein the resin component includes a double bond-containing curable polymer, and the double bond equivalent of the double bond-containing curable polymer is 200 g / eq. or more and 350 g / eq. or less.
[0015] The present invention [7] includes a molded article comprising a cured product of the thin plate molding material according to any one of the above [1] to [6] and having a thickness of 1.5 mm or less. Effect of the Invention
[0016] The thin plate molding material of the present invention comprises a resin composition containing a resin component and a filler, and reinforcing fibers having a predetermined fiber length, the content ratio of the reinforcing fibers is a predetermined ratio, and the blending ratio of the resin component is a predetermined ratio.
[0017] Therefore, it is possible to mold a molded product that has excellent formability (thin plate formability) for a mold that requires a thin plate, and has excellent specific strength and specific rigidity that provide the strength and rigidity of a part even with a thin plate.
[0018] The molded article of the present invention contains a cured product of the sheet molding material of the present invention, and therefore the specific strength, specific rigidity and sheet formability of the material result in a lightweight part that satisfies the strength and rigidity required of the part. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0019] The thin plate molding material of the present invention contains a resin composition and reinforcing fibers having a predetermined fiber length.
[0020] The resin composition includes a resin component and a filler.
[0021] The resin component includes a double bond-containing curable polymer and a polymerizable monomer.
[0022] Examples of the double bond-containing curable polymer include unsaturated polyesters and vinyl esters.
[0023] Unsaturated polyesters are the polymerization products of polybasic acids and polyhydric alcohols.
[0024] The polybasic acid includes a polybasic acid having an ethylenically unsaturated double bond as an essential component (hereinafter referred to as an ethylenically unsaturated bond-containing polybasic acid) and a polybasic acid not having an ethylenically unsaturated double bond as an optional component (hereinafter referred to as an ethylenically unsaturated bond-free polybasic acid).
[0025] Examples of the ethylenically unsaturated bond-containing polybasic acid include ethylenically unsaturated aliphatic dibasic acids such as maleic acid, fumaric acid, itaconic acid, and dihydromuconic acid, as well as halides of these acids and alkyl esters of these acids.
[0026] Furthermore, the ethylenically unsaturated bond-containing polybasic acid includes acid anhydrides derived from the above ethylenically unsaturated aliphatic dibasic acids, such as maleic anhydride.
[0027] Preferred examples of the ethylenically unsaturated bond-containing polybasic acid include maleic anhydride and fumaric acid.
[0028] Examples of polybasic acids not containing ethylenically unsaturated bonds include saturated aliphatic polybasic acids, saturated alicyclic polybasic acids, aromatic polybasic acids, halides of these acids, and alkyl esters of these acids.
[0029] Examples of saturated aliphatic polybasic acids include saturated aliphatic dibasic acids such as oxalic acid, malonic acid, succinic acid, methylsuccinic acid, 2,2-dimethylsuccinic acid, 2,3-dimethylsuccinic acid, hexylsuccinic acid, glutaric acid, 2-methylglutaric acid, 3-methylglutaric acid, 2,2-dimethylglutaric acid, 3,3-dimethylsuccinic acid, adipic acid, pimelic acid, suberic acid, azelaic acid, and sebacic acid.
[0030] The saturated aliphatic polybasic acids also include acid anhydrides derived from the above-mentioned saturated aliphatic dibasic acids, such as oxalic anhydride and succinic anhydride.
[0031] Examples of saturated alicyclic polybasic acids include saturated alicyclic dibasic acids such as HET acid, 1,2-hexahydrophthalic acid, 1,1-cyclobutanedicarboxylic acid, 1,4-cyclohexanedicarboxylic acid (cis- or trans-1,4-cyclohexanedicarboxylic acid or a mixture thereof), and dimer acid.
[0032] The saturated alicyclic polybasic acids include acid anhydrides derived from the above-mentioned saturated alicyclic dibasic acids, such as HET anhydride.
[0033] Examples of aromatic polybasic acids include aromatic dibasic acids such as phthalic acid (orthophthalic acid, isophthalic acid, terephthalic acid), trimellitic acid, and pyromellitic acid.
[0034] The aromatic polybasic acids also include acid anhydrides derived from the above aromatic dibasic acids, such as phthalic anhydride.
[0035] As the polybasic acid not containing an ethylenically unsaturated bond, preferably, an aromatic polybasic acid is used, more preferably, an aromatic dibasic acid is used, further preferably, phthalic acid is used, and particularly preferably, isophthalic acid is used.
[0036] The polybasic acids can be used alone or in combination of two or more kinds.
[0037] In addition, when an ethylenically unsaturated bond-containing polybasic acid and an ethylenically unsaturated bond-free polybasic acid are used in combination, the blending ratio of the ethylenically unsaturated bond-containing polybasic acid to the polybasic acid is, for example, 40 mol % or more and, for example, 70 mol % or less.
[0038] Examples of polyhydric alcohols include alkane diols such as ethylene glycol, propylene glycol (1,2- or 1,3-propanediol or a mixture thereof), butylene glycol (1,2-, 1,3-, or 1,4-butylene glycol or a mixture thereof), 1,5-pentanediol, 1,6-hexanediol, neopentyl glycol, 2-methyl-1,3-propanediol, 2-butyl-2-ethyl-1,3-propanediol, 3-methyl-1,5-pentanediol, 2,2,2-trimethylpentanediol, and 3,3-dimethylolheptane; aliphatic diols such as ether diols such as diethylene glycol, triethylene glycol, and dipropylene glycol; cyclohexane diols (1,2-, 1,3-, or 1,4-cyclohexanediol or a mixture thereof), cyclohexane dimethanol (1,2-, 1,3-, or 1,4-cyclohexane dimethanol or a mixture thereof); Examples of the alcohol include cyclohexanediethanol (1,2- or 1,3- or 1,4-cyclohexanediethanol or a mixture thereof), alicyclic diols such as hydrogenated bisphenol A, aromatic diols such as bisphenol A, ethylene oxide adducts of bisphenol A, and propylene oxide adducts of bisphenol A, trihydric alcohols such as glycerin, trimethylolpropane, and triisopropanolamine, tetrahydric alcohols such as tetramethylolmethane (pentaerythritol) and diglycerin, pentahydric alcohols such as xylitol, and hexahydric alcohols such as sorbitol, mannitol, allitol, iditol, dulcitol, altritol, inositol, and dipentaerythritol. Of these, preferably, dihydric alcohols are used, more preferably, aliphatic diols are used, and even more preferably, alkanediols are used, and particularly preferably, propylene glycol and neopentyl glycol are used.
[0039] The polyhydric alcohols can be used alone or in combination of two or more kinds.
[0040] The unsaturated polyester can be obtained by polycondensation (condensation polymerization) of a polybasic acid and a polyhydric alcohol.
[0041] To polycondense (condensation polymerize) a polybasic acid and a polyhydric alcohol, they are mixed so that the equivalent ratio of the polyhydric alcohol to the polybasic acid (hydroxyl groups of the polyhydric alcohol / carboxyl groups of the polybasic acid) is, for example, 0.9 or more, preferably 0.95 or more, and for example, 1.2 or less, preferably 1.1 or less, and stirred at normal pressure in a nitrogen atmosphere.
[0042] The reaction temperature is, for example, 150° C. or more, preferably 190° C. or more, and for example, 250° C. or less, preferably 230° C. or less.
[0043] The reaction time is, for example, 8 hours or more and, for example, 30 hours or less.
[0044] In the above reaction, a known solvent and a known catalyst can be added, if necessary.
[0045] This gives an unsaturated polyester.
[0046] The acid value of the unsaturated polyester (measurement method: in accordance with JIS K6901 (2008)) is, for example, 20 mgKOH / g or more, preferably 25 mgKOH / g or more, and for example, less than 40 mgKOH / g, preferably 30 mgKOH / g or less.
[0047] The weight average molecular weight of the unsaturated polyester is, for example, 4,000 or more, preferably 6,000 or more, and for example, 25,000 or less, preferably 20,000 or less.
[0048] The weight average molecular weight is a weight average molecular weight converted into polystyrene by GPC (gel permeation chromatography), and can be determined by subjecting the unsaturated polyester to GPC measurement.
[0049] Vinyl esters are the reaction products of epoxy resins and unsaturated monobasic acids.
[0050] Examples of the epoxy resin include bisphenol type epoxy resins and novolac type epoxy resins, and preferably bisphenol type epoxy resins.
[0051] The bisphenol type epoxy resin is represented by the following general formula (1).
[0052] [ka]
[0053] (In the formula, Y 1 represents any one of -C(CH3)2-, -CH2-, -O-, -S-, and -(O=S=O)-, and n represents an integer of 0 to 5. Examples of such bisphenol type epoxy resins include bisphenol A type epoxy resins, bisphenol F type epoxy resins, and bisphenol S type epoxy resins, and preferably bisphenol A type epoxy resins.
[0054] The epoxy resin can also be modified with a phenolic compound such as bisphenol A, bisphenol F, or bisphenol S.
[0055] In order to modify an epoxy resin with a phenolic compound, the epoxy resin is reacted with the phenolic compound.
[0056] The mixing ratio of the phenol compound is, for example, 0.1 mol or more, preferably 0.2 mol or more, and for example, 0.5 mol or less, relative to 1 mol of the epoxy resin.
[0057] In the above reaction, the reaction temperature is, for example, 100° C. or more, preferably 130° C. or more, and for example, 170° C. or less, and the reaction time is, for example, 1 hour or more, preferably 2 hours or more, and for example, 10 hours or less.
[0058] In the above reaction, a catalyst can be added, if necessary.
[0059] Examples of the catalyst include amines such as triethylamine and benzyldimethylamine; ammonium salts such as tetramethylammonium chloride and triethylbenzylammonium chloride; imidazoles such as 2-ethyl-4-imidazole; amides, pyridines, phosphines such as triphenylphosphine; phosphonium salts such as tetraphenylphosphonium bromide and ethyltriphenylphosphonium bromide; sulfonium salts, such as sulfonic acids; and organic metal salts such as zinc octylate. Preferably, the catalyst is an ammonium salt, and more preferably, triethylbenzylammonium chloride.
[0060] The catalysts can be used alone or in combination of two or more kinds.
[0061] The mixing ratio of the catalyst is, for example, 0.1 parts by mass or more and, for example, 3 parts by mass or less, preferably 1 part by mass or less, relative to 100 parts by mass of the epoxy resin.
[0062] This allows the epoxy resin to be modified with the phenol compound.
[0063] As the epoxy resin, preferably, an epoxy resin modified with a phenol compound is used, and more preferably, a bisphenol A type epoxy resin modified with bisphenol A is used.
[0064] The epoxy resins can be used alone or in combination of two or more kinds.
[0065] The epoxy equivalent of the epoxy resin is, for example, 100 mgKOH / g or more, preferably 250 mgKOH / g or more, and for example, 500 mgKOH / g or less, preferably 350 mgKOH / g or less.
[0066] In addition, when two types of epoxy resins are used in combination, the above epoxy equivalent is the epoxy equivalent of all epoxy resins, calculated by multiplying the epoxy equivalent of each epoxy resin by the mass ratio of each epoxy resin to the total amount of epoxy resins, and adding them together.
[0067] Examples of unsaturated monobasic acids include monocarboxylic acids such as (meth)acrylic acid, crotonic acid, cinnamic acid, and sorbic acid, and reaction products of dibasic acid anhydrides with alcohols having at least one unsaturated group in the molecule. Note that (meth)acrylic is synonymous with methacrylic and / or acrylic.
[0068] Examples of dibasic acid anhydrides include maleic anhydride, succinic anhydride, phthalic anhydride, tetrahydrophthalic anhydride, and hexahydrophthalic anhydride.
[0069] Examples of the alcohol having an unsaturated group include hydroxyethyl (meth)acrylate, hydroxypropyl (meth)acrylate, hydroxybutyl (meth)acrylate, pentaerythritol tri(meth)acrylate, and glycerin di(meth)acrylate.
[0070] The unsaturated monobasic acids can be used alone or in combination of two or more kinds.
[0071] As the unsaturated monobasic acid, preferably, a monocarboxylic acid is used, more preferably, (meth)acrylic acid is used, and further preferably, methacrylic acid is used.
[0072] To obtain the vinyl ester, an epoxy resin is reacted with an unsaturated monobasic acid.
[0073] In the above reaction, an addition reaction occurs between the epoxy group of the epoxy resin and the unsaturated monobasic acid.
[0074] In the above reaction, the equivalent of the carboxyl group of the unsaturated monobasic acid to the epoxy group of the epoxy resin is, for example, 0.8 or more, preferably 0.9 or more, and for example, 1.5 or less, preferably 1.1 or less.
[0075] In the above reaction, the reaction temperature is, for example, 80° C. or more, preferably 100° C. or more, and for example, 150° C. or less, preferably 130° C. or less, and the reaction time is, for example, 1 hour or more, preferably 2 hours or more, and for example, 10 hours or less.
[0076] In the above reaction, the above catalyst (preferably an ammonium salt, more preferably triethylbenzylammonium chloride) can be added, if necessary.
[0077] The mixing ratio of the catalyst is, relative to 100 parts by mass of the epoxy resin, for example, 0.1 parts by mass or more, preferably 1 part by mass or more, and for example, 5 parts by mass or less, preferably 3 parts by mass or less.
[0078] In the above reaction, a polymerization inhibitor can be added, if necessary.
[0079] Examples of the polymerization inhibitor include hydroquinone compounds such as hydroquinone, methylhydroquinone, and t-butylhydroquinone, benzoquinone compounds such as p-benzoquinone and methyl-p-benzoquinone, catechol compounds such as t-butylcatechol, phenol compounds such as 2,6-di-t-butyl-4-methylphenol and 4-methoxyphenol, and 1-oxyl-2,2,6,6-tetramethylpiperidine, 1-oxyl-2,2,6,6-tetramethylpiperidin-4-ol, 4-hydroxy-2,2, 6,6-tetrapiperidine-1-oxyl, 4-methoxy-2,2,6,6-tetramethylpiperidine-1-oxyl, 1-oxyl-2,2,6,6-tetramethylpiperidin-4-yl-acetate, 1-oxyl-2,2,6,6-tetramethylpiperidin-4-yl-2-ethylhexanoate, 1-oxyl-2,2,6,6-tetramethylpiperidin-4-yl-stearate, 1-oxyl-2,2,6,6-tetramethylpiperidin-4-yl-4-t-butylbenzoate, bis(1-oxyl-2,2,6,6-tetramethylpiperidinyl) Bis(1-oxyl-2,2,6,6-tetramethylpiperidin-4-yl) succinate, bis(1-oxyl-2,2,6,6-tetramethylpiperidin-4-yl) adipate, bis(1-oxyl-2,2,6,6-tetramethylpiperidin-4-yl) sebacate, bis(1-oxyl-2,2,6,6-tetramethylpiperidin-4-yl) n-butylmalonate, bis(1-oxyl-2,2,6,6-tetramethylpiperidin-4-yl) phthalate, bis(1-oxyl-2,2,6,6-tetramethylpiperidin-4-yl) isophthalate, bis(1-oxyl-2,2,6 ,6-tetramethylpiperidin-4-yl) terephthalate, bis(1-oxyl-2,2,6,6-tetramethylpiperidin-4-yl) hexahydroterephthalate, N,N'-bis(1-oxyl-2,2,6,6-tetramethylpiperidin-4-yl) adipamide, N-bis(1-oxyl-2,2,6,6-tetramethylpiperidin-4-yl) caprolactam, N-bis(1-oxyl-2,2,6,6-tetramethylpiperidin-4-yl) dodecyl succinimide, 2,4,6-tris-[N-butyl-N-(1-oxyl-2,2,6,Examples of the N-oxyl compounds include N-oxyl compounds such as 1-oxyl-2,2,6,6-tetramethylpiperidin-4-yl)-s-triazine and 1-oxyl-2,2,6,6-tetramethylpiperidin-4-one, and preferably, hydroquinone compounds, and more preferably, hydroquinone.
[0080] The polymerization inhibitors can be used alone or in combination of two or more kinds.
[0081] The mixing ratio of the polymerization inhibitor relative to 100 parts by mass of the epoxy resin is, for example, 0.1 parts by mass or more, preferably 1 part by mass or more, and for example, 5 parts by mass or less, preferably 3 parts by mass or less.
[0082] This gives a vinyl ester.
[0083] The acid value of the vinyl ester (measurement method: in accordance with JIS K6901 (2008)) is, for example, 1 mgKOH / g or more, preferably 5 mgKOH / g or more, and for example, less than 20 mgKOH / g, preferably 10 mgKOH / g or less.
[0084] The double bond-containing curable polymers can be used alone or in combination of two or more kinds.
[0085] The double bond equivalent (number average molecular weight per double bond) of the double bond-containing curable polymer is, for example, 150 g / eq. or more, preferably 200 g / eq. or more, and for example, 450 g / eq. or less, preferably 350 g / eq. or less.
[0086] When the double bond equivalent of the double bond-containing curable polymer is equal to or more than the above lower limit, a molded article (described later) having excellent toughness even if it is thin and excellent strength (specific strength) can be molded.
[0087] In addition, when the double bond equivalent of the double bond-containing curable polymer is equal to or less than the above upper limit, it is possible to form a molded product (described later) that is excellent in heat resistance, does not crack even when demolded at high temperatures during molding, and has excellent strength (specific strength) and elastic modulus (specific rigidity) even when it is thin.
[0088] The method for calculating the double bond equivalent will be described in detail in the Examples below.
[0089] In addition, when two types of double bond-containing curable polymers are used in combination, the above double bond equivalent is calculated based on the definition from the double bond equivalent and blending ratio of each double bond-containing curable polymer. More specifically, for example, when the double bond equivalents of polymers A and B are eqA (g / eq.) and eqB (g / eq.), and the ratio of the parts by mass of the polymers used in combination is a:b, the double bond equivalent of the combined polymer is calculated by the following formula (1).
[0090] [(a / (a+b) / eqA)+(b / (a+b) / eqB)] -1 (1) The double bond-containing curable polymers can be used alone or in combination of two or more kinds.
[0091] When an unsaturated polyester and a vinyl ester are used in combination as the double bond-containing curable polymer, the blending ratio of the unsaturated polyester is, for example, 50 parts by mass or more and, for example, 90 parts by mass or less, relative to 100 parts by mass of the total amount of the unsaturated polyester and the vinyl ester, and the blending ratio of the vinyl ester is, for example, 10 parts by mass or more and, for example, 50 parts by mass or less, relative to 100 parts by mass of the total amount of the unsaturated polyester and the vinyl ester.
[0092] The mixing ratio of the double bond-containing curable polymer is, for example, 30 parts by mass or more and, for example, 60 parts by mass or less, relative to 100 parts by mass of the total amount of the double bond-containing curable polymer, the polymerizable monomer, and the low shrinkage agent (described later) that is mixed as necessary.
[0093] The polymerizable monomer is a solvent for dissolving the double bond-containing curable polymer, and is also a crosslinkable monomer (reactive diluent) that can crosslink with the double bond-containing curable polymer when the double bond-containing curable resin (described later) is cured. Examples of the polymerizable monomer include styrene-based monomers such as styrene, α-methylstyrene, α-ethylstyrene, vinyltoluene, t-butylstyrene, and chlorostyrene; methyl (meth)acrylate, ethyl (meth)acrylate, isopropyl (meth)acrylate, butyl (meth)acrylate, n-butyl (meth)acrylate; (Meth)acrylic acid alkyl esters such as t-butyl (meth)acrylate, isobutyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, lauryl (meth)acrylate, tridecyl (meth)acrylate, and stearyl (meth)acrylate; (meth)acrylic acid allyl esters such as allyl (meth)acrylate; (meth)acrylic acid cyclohexyl, benzyl (meth)acrylate, isobornyl (meth)acrylate, glycidyl (meth)acrylate, tetrahydrofurfuryl (meth)acrylate, and the like. ) (meth)acrylic acid esters containing a ring structure such as dicyclopentenyl acrylate, dicyclopentanyl (meth)acrylate, and dicyclopentenyloxyethyl (meth)acrylate; (meth)acrylic acid hydroxyalkyl esters such as 2-hydroxyethyl (meth)acrylate and 2-hydroxypropyl (meth)acrylate; (meth)acrylic acid alkoxyalkyl esters such as 2-methoxyethyl (meth)acrylate and 2-ethoxyethyl (meth)acrylate; (meth)acrylic acid aminoalkyl esters and chloride salts thereof such as dimethylaminoethyl (meth)acrylate and diethylaminoethyl (meth)acrylate; (meth)acrylic acid fluoroalkyl esters such as trifluoroethyl (meth)acrylate and heptadecafluorodecyl (meth)acrylate; (meth)acrylic acid ester monomers such as ethylene glycol di(meth)acrylate, diethylene glycol di(meth)acrylate, trimethylolpropane tri(meth)acrylate, and pentaerythritol tetra(meth)acrylate;Examples of the monomer include polyfunctional (meth)acrylic acid esters such as dipentaerythritol hexa(meth)acrylate, and allyl monomers such as glycerin monoallyl ether, pentaerythritol diallyl ether, pentaerythritol monoallyl ether, and trimethylolpropane monoallyl ether. Of these, preferred are styrene monomers, and more preferred are styrene.
[0094] The polymerizable monomers can be used alone or in combination of two or more kinds.
[0095] The mixing ratio of the polymerizable monomer is, for example, 30 parts by mass or more, preferably 100 parts by mass or more, and for example, 150 parts by mass or less, relative to 100 parts by mass of the double bond-containing curable polymer.
[0096] The blending ratio of the polymerizable monomer is, for example, 20 parts by mass or more, preferably 30 parts by mass or more, and for example, 60 parts by mass or less, relative to 100 parts by mass of the total amount of the double bond-containing curable polymer, the polymerizable monomer, and the low shrinkage agent (described later) blended as necessary.
[0097] The resin component preferably also contains a low shrinkage agent.
[0098] The low shrinkage agent is blended in order to suppress cure shrinkage and heat shrinkage of a molded article (described later) obtained by using this thin plate molding material.
[0099] Examples of the low shrinkage agent include polyethylene, polystyrene, styrene-based thermoplastic elastomers, crosslinked polystyrene, polyvinyl acetate-polystyrene block copolymers, polyvinyl acetate, polymethyl methacrylate, and saturated polyester resins.
[0100] Examples of styrene-based thermoplastic elastomers include styrene-butadiene block copolymer elastomers, styrene-isoprene block copolymer elastomers, styrene-ethylene / butylene block copolymer elastomers, and styrene-ethylene / propylene block copolymer elastomers, and preferably, styrene-ethylene / propylene block copolymer elastomers. Commercially available styrene-based thermoplastic elastomers include D1101, D1102, D1155, DKX405, DKX410, DKX415, D1192, D1161, D1171, G1651, G1652, G1654, G1701, and G1730 (all manufactured by Kraton Elastomers), Asaprene T411, Asaprene T432, Tufprene A, Tufprene 125, Tufprene 126S, Tufprene 315, Tufprene 912, Tuftec H1141, Tuftec H1041, Tuftec H1043, and Tuftec H1052 (all manufactured by Asahi Kasei Corporation), and Septon 1001 and 1201 (all manufactured by Kuraray Co., Ltd.).
[0101] The styrene content in the styrene-based thermoplastic elastomer is, for example, 5% by mass or more and, for example, 50% by mass or less.
[0102] As the shrinkage reducing agent, preferably, polyethylene, polystyrene, and polyvinyl acetate are used.
[0103] The low profile agents can be used alone or in combination of two or more.
[0104] The mixing ratio of the low shrinkage agent relative to 100 parts by mass of the double bond-containing curable polymer is, for example, 5 parts by mass or more, preferably 20 parts by mass or more, and for example, 50 parts by mass or less.
[0105] The mixing ratio of the low shrinkage agent is, for example, 3 parts by mass or more, preferably 5 parts by mass or more, and for example, 25 parts by mass or less, preferably 15 parts by mass or less, relative to 100 parts by mass of the total amount of the double bond-containing curable polymer, the polymerizable monomer, and the low shrinkage agent.
[0106] The filling material preferably contains a filler (hereinafter referred to as a first filler) having an average maximum length of 15 μm or more and 300 μm or less.
[0107] If the filling material contains a first filler, it is possible to produce a molded product (described below) that has excellent formability (thin plate formability) for a mold that requires a thin plate, and that has excellent specific strength and specific rigidity that provide the strength and rigidity of a part even when made from a thin plate.
[0108] The average value of the maximum length is the average particle diameter d that can be obtained by creating a particle diameter distribution curve using a laser diffraction / scattering type particle diameter distribution analyzer and calculating the 50% by mass equivalent particle diameter if the filler is substantially spherical (specifically, glass balloons (hollow glass) (described later)). 50 Furthermore, if the filler has a needle-like shape (specifically, milled carbon fiber (described later)), the fiber length distribution is determined for an appropriate amount of milled carbon fiber using a videoscope, and the length-weighted average fiber length Lw is calculated using the frequency Ni and average length Li of each histogram according to the following formula (2). Lw = Σ(NiLi 2 / NiLi) (2) Examples of materials for the first filler include oxides such as alumina and titania, hydroxides such as magnesium hydroxide and aluminum hydroxide, carbonates such as calcium carbonate, sulfates such as barium sulfate, silica (e.g., crystalline silica, fused silica, fumed silica, dry silica (aerosil), etc.), glass powder, hollow fillers such as glass balloons (hollow glass), silica balloons, and alumina balloons, silicates such as silica sand, diatomaceous earth, mica, clay, kaolin, and talc, fluorides such as fluorite, phosphates such as calcium phosphate, inorganic fillers such as clay minerals such as smectite, carbon fibers such as milled carbon fibers, conductive particles, and conductive fillers such as carbon nanotubes, and preferably hollow fillers and carbon fibers, and more preferably glass balloons (hollow glass) and milled carbon fibers.
[0109] When the material of the first filler is glass balloons (hollow glass), the average maximum length of the glass balloons (hollow glass) is, for example, 15 μm or more, and, for example, 300 μm or less, preferably 100 μm or less, and more preferably 50 μm or less.
[0110] If the filler contains glass balloons (hollow glass) having an average maximum length of 15 μm or more and 50 μm or less as the first filler, the density can be reduced without impairing the formability into thin sheets, and a molded product (described later) with excellent specific strength and specific rigidity can be molded.
[0111] Furthermore, when the material of the first filler is milled carbon fiber, the average maximum length of the milled carbon fiber is, for example, 100 μm or more and, for example, 300 μm or less.
[0112] When the filling material contains milled carbon fiber having an average maximum length of 100 μm or more and 300 μm or less as the first filler, the strength and elastic modulus are improved without affecting the thin plate formability or density, and a molded product (described later) with excellent specific strength and specific rigidity can be produced.
[0113] The first filler may be used alone or in combination of two or more kinds, and preferably contains the above-mentioned glass balloons (hollow glass) and the above-mentioned milled carbon fibers.
[0114] When the first filler contains the glass balloons (hollow glass) and the milled carbon fiber, the blending ratio of the glass balloons (hollow glass) is, for example, 60 parts by mass or more and, for example, 80 parts by mass or less, and the blending ratio of the milled carbon fiber is, for example, 20 parts by mass or more and, for example, 40 parts by mass or less, relative to a total of 100 parts by mass of the glass balloons (hollow glass) and the milled carbon fiber.
[0115] The mixing ratio of the first filler is, for example, 5 parts by mass or more, preferably 20 parts by mass or more, more preferably 30 parts by mass or more, and even more preferably 40 parts by mass or more, relative to 100 parts by mass of the filler, and for example, 60 parts by mass or less, preferably 50 parts by mass or less.
[0116] The mixing ratio of the first filler is, for example, 3 parts by mass or more, preferably 10 parts by mass or more, and for example, 50 parts by mass or less, preferably 20 parts by mass or less, relative to 100 parts by mass of the total amount of the double bond-containing curable polymer, the polymerizable monomer, and the low shrinkage agent mixed as necessary.
[0117] The filling material may also include a filler (hereinafter referred to as a second filler) having an average maximum length of less than 15 μm.
[0118] Examples of the material for the second filler include the above-mentioned materials for the first filler, and preferably, calcium carbonate is used.
[0119] The second filler may be used alone or in combination of two or more kinds.
[0120] The mixing ratio of the second filler is, for example, 40 parts by mass or more, preferably 50 parts by mass or more, and for example, 95 parts by mass or less, preferably 80 parts by mass or less, more preferably 70 parts by mass or less, and even more preferably 60 parts by mass or less, relative to 100 parts by mass of the filler.
[0121] The mixing ratio of the second filler is, for example, 10 parts by mass or more, preferably 20 parts by mass or more, and for example, 150 parts by mass or less, preferably 100 parts by mass or less, more preferably 50 parts by mass or less, relative to 100 parts by mass of the total amount of the double bond-containing curable polymer, the polymerizable monomer, and the low shrinkage agent mixed as necessary.
[0122] The filling material may also include a filler (hereinafter referred to as a third filler) having an average maximum length exceeding 300 μm.
[0123] The material of the third filler may be the same as the material of the first filler described above.
[0124] The third filler may be used alone or in combination of two or more kinds.
[0125] The mixing ratio of the third filler relative to 100 parts by mass of the filler is, for example, 1 part by mass or more, preferably 10 parts by mass or more, and for example, 100 parts by mass or less, preferably 50 parts by mass or less.
[0126] The mixing ratio of the third filler is, for example, 10 parts by mass or more and, for example, 50 parts by mass or less, relative to 100 parts by mass of the total amount of the double bond-containing curable polymer, the polymerizable monomer, and the low shrinkage agent mixed as necessary.
[0127] The filler preferably includes a first filler and a second filler, but does not include a third filler.
[0128] The mixing ratio of the filler relative to 100 parts by mass of the double bond-containing curable polymer is, for example, 60 parts by mass or more, preferably 80 parts by mass or more, and for example, 400 parts by mass or less, preferably 200 parts by mass or less.
[0129] The mixing ratio of the filler is, relative to 100 parts by mass of the total amount of the double bond-containing curable polymer, the polymerizable monomer, and the low shrinkage agent mixed as necessary, is, for example, 30 parts by mass or more, preferably 40 parts by mass or more, and for example, 150 parts by mass or less, preferably 100 parts by mass or less, 60 parts by mass or less, and more preferably 50 parts by mass or less.
[0130] Furthermore, the resin component may contain additives such as polymerization inhibitors, curing catalysts, silane coupling agents, wetting and dispersing agents, release agents, thickeners, colorants, flame retardants, etc. These additives may be used alone or in combination of two or more kinds.
[0131] As the polymerization inhibitor, the above-mentioned polymerization inhibitors can be used, and preferably, p-benzoquinone can be used.
[0132] The mixing ratio of the polymerization inhibitor is, for example, 0.01 parts by mass or more and, for example, 5 parts by mass or less, preferably 1 part by mass or less, relative to 100 parts by mass of the total amount of the double bond-containing curable polymer, the polymerizable monomer, and the low shrinkage agent mixed as necessary.
[0133] Examples of the curing catalyst include peroxides such as benzoyl peroxide, t-butylperoxyisopropyl monocarbonate, t-amylperoxyisopropyl carbonate, t-hexylperoxyisopropyl monocarbonate, 1,1-bis(t-butylperoxy)cyclohexane, t-butylperoxy-2-ethylhexanoate, amylperoxy-2-ethylhexanoate, 2-ethylhexylperoxy-2-ethylhexanoate, t-butylperoxybenzoate, t-hexylperoxybenzoate, and t-hexylperoxyacetate. Preferred are peroxyisopropyl monocarbonates such as t-butylperoxyisopropyl monocarbonate, t-amylperoxyisopropyl monocarbonate, t-hexylperoxyisopropyl monocarbonate, and t-butylperoxybenzoate. Preferred is t-butylperoxyisopropyl carbonate.
[0134] The mixing ratio of the curing catalyst is, relative to 100 parts by mass of the total amount of the double bond-containing curable polymer, the polymerizable monomer, and the low shrinkage agent mixed as necessary, is, for example, 0.5 parts by mass or more, preferably 1 part by mass or more, and for example, 10 parts by mass or less, preferably 3 parts by mass or less.
[0135] The curing catalysts can be used alone or in combination of two or more kinds.
[0136] Silane coupling agents are blended to increase the mechanical strength and water resistance of molded articles (described later). Examples of coupling agents include silane coupling agents having a vinyl group such as vinyltrichlorosilane and vinyltriethoxysilane, silane coupling agents having an epoxy group such as 3-glycidoxypropyltrimethoxysilane and 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, silane coupling agents having an amino group such as 3-aminopropyltrimethoxysilane and N-2-(aminoethyl)-3-aminopropyltriethoxysilane, silane coupling agents having a (meth)acryloyl group such as 3-methacryloxypropyltrimethoxysilane and 3-methacryloxypropylmethyldimethoxysilane, and titanate-based coupling agents, and preferably silane coupling agents having a (meth)acryloyl group, and more preferably 3-methacryloxypropyltrimethoxysilane.
[0137] The silane coupling agents can be used alone or in combination of two or more kinds.
[0138] The blending ratio of the silane coupling agent is, for example, 0.1 parts by mass or more, preferably 0.5 parts by mass or more, and for example, 5 parts by mass or less, preferably 1 part by mass or less, relative to 100 parts by mass of the total amount of the double bond-containing curable polymer, the polymerizable monomer, and the low shrinkage agent blended as necessary.
[0139] The silane coupling agents can be used alone or in combination of two or more kinds.
[0140] The wetting dispersant is blended to reduce the viscosity of the resin composition to a level suitable for heat compression molding, and examples of the wetting dispersant include known wetting dispersants such as polyester phosphate. In addition, commercially available wetting dispersants can be used, and specifically, BYK-W996 (manufactured by BYK-Chemie) and the like are used.
[0141] The mixing ratio of the wetting dispersant is, relative to 100 parts by mass of the total amount of the double bond-containing curable polymer, the polymerizable monomer, and the low shrinkage agent mixed as necessary, is, for example, 0.1 parts by mass or more, preferably 0.5 parts by mass or more, and for example, 10 parts by mass or less, preferably 3 parts by mass or less.
[0142] The wetting and dispersing agents can be used alone or in combination of two or more kinds.
[0143] Examples of the release agent include fatty acids such as stearic acid and lauric acid, fatty acid metal salts such as zinc stearate and calcium stearate, paraffin, liquid wax, fluoropolymers, and silicon-based polymers, and preferably fatty acid metal salts, and more preferably zinc stearate.
[0144] The mixing ratio of the release agent is, for example, 1 part by mass or more, preferably 3 parts by mass or more, and for example, 10 parts by mass or less, relative to 100 parts by mass of the total amount of the double bond-containing curable polymer, the polymerizable monomer, and the low shrinkage agent mixed as necessary.
[0145] The release agents can be used alone or in combination of two or more kinds.
[0146] The thickener is blended in order to thicken the resin composition to a viscosity suitable for heat compression molding, and is preferably blended before (preferably immediately before) impregnating the resin composition into reinforcing fibers (described later). Examples of the thickener include alkaline earth metal oxides such as magnesium oxide, alkaline earth metal hydroxides such as magnesium hydroxide and calcium hydroxide, and polyisocyanate compounds such as diphenylmethane diisocyanate (MDI), and preferably alkaline earth metal oxides, and more preferably magnesium oxide.
[0147] The blending ratio of the thickener is, for example, 0.1 parts by mass or more, preferably 0.5 parts by mass or more, and for example, 5 parts by mass or less, preferably 3 parts by mass or less, relative to 100 parts by mass of the total amount of the double bond-containing curable polymer, the polymerizable monomer, and the low shrinkage agent blended as necessary.
[0148] The thickeners can be used alone or in combination of two or more kinds.
[0149] The colorant is not particularly limited, and examples thereof include titanium oxide, polyester toner (polyester colorant containing titanium oxide and / or carbon black), and the like.
[0150] The blending ratio of the colorant is, for example, 1 part by mass or more, preferably 5 parts by mass or more, and for example, 20 parts by mass or less, relative to 100 parts by mass of the total amount of the double bond-containing curable polymer, the polymerizable monomer, and the low shrinkage agent blended as necessary.
[0151] The colorants can be used alone or in combination of two or more kinds.
[0152] Examples of the flame retardant include halogen-based flame retardants such as bromine-based flame retardants, and non-halogen-based flame retardants such as phosphorus-based flame retardants, inorganic flame retardants, and nitrogen compound-based flame retardants.
[0153] The blending ratio of the flame retardant is, for example, 1 part by mass or more, preferably 5 parts by mass or more, and for example, 50 parts by mass or less, preferably 20 parts by mass or less, relative to 100 parts by mass of the total amount of the double bond-containing curable polymer, the polymerizable monomer, and the low shrinkage agent blended as necessary.
[0154] The flame retardants can be used alone or in combination of two or more kinds.
[0155] In addition, the resin component may contain additives such as a pattern material, an antibacterial agent, a hydrophilic agent, a photocatalyst, an ultraviolet absorber, an ultraviolet stabilizer, an anti-separation agent, an antistatic agent, a thixotropic agent, a thixotropic stabilizer, and a polymerization accelerator, as necessary, within the range that does not impair the effects of the present invention. These additives may be used alone or in combination of two or more kinds.
[0156] The resin composition can be obtained by blending each component of the resin component (specifically, the double bond-containing curable polymer, the polymerizable monomer, the low shrinkage agent blended as necessary, and various additives blended as necessary) with the filler in the blending ratio described above.
[0157] This results in a resin composition.
[0158] In such a resin composition, the mixing ratio of the double bond-containing curable polymer is, for example, 10 mass% or more, preferably 20 mass% or more, and for example, 40 mass% or less, preferably 30 mass% or less, relative to the resin composition.
[0159] The mixing ratio of the polymerizable monomer is, for example, 15 mass % or more, preferably 25 mass % or more, and for example, 55 mass % or less, relative to the resin composition.
[0160] The mixing ratio of the low shrinkage agent relative to the resin composition is, for example, 3 mass % or more, preferably 5 mass % or more, and for example, 15 mass % or less, preferably 10 mass % or less.
[0161] The mixing ratio of the resin component is, with respect to the resin composition, for example, 40 mass % or more, preferably 50 mass % or more, and for example, 80 mass % or less, preferably 70 mass % or less.
[0162] The mixing ratio of the filler relative to the resin composition is, for example, 10 mass % or more, preferably 20 mass % or more, and for example, 70 mass % or less, preferably 50 mass % or less.
[0163] In the above description, the double bond-containing curable polymer, the polymerizable monomer, the low profile agent which is blended as necessary, the additive which is blended as necessary, and the filler are blended to obtain a resin composition. However, it is also possible to first prepare a double bond-containing curable resin by dissolving the double bond-containing curable polymer in the polymerizable monomer, and then blend the obtained double bond-containing curable resin with the polymerizable monomer, the low profile agent which is blended as necessary, the additive which is blended as necessary, and the filler.
[0164] In preparing the double bond-containing curable polymer, the double bond-containing curable polymer and the polymerizable monomer are mixed, and the above-mentioned additives can also be mixed appropriately, if necessary.
[0165] In preparing the double bond-containing curable polymer, the mixing ratio of the polymerizable monomer is, for example, 35 parts by mass or more and, for example, 150 parts by mass or less, based on 100 parts by mass of the double bond-containing curable polymer.
[0166] Examples of reinforcing fibers include inorganic fibers such as glass fibers, carbon fibers, metal fibers, and ceramic fibers; organic fibers such as polyvinyl alcohol fibers, polyester fibers, polyamide fibers, fluororesin fibers, and phenol fibers; and natural fibers such as hemp and kenaf. Preferably, inorganic fibers are used, more preferably carbon fibers and glass fibers, and even more preferably glass fibers.
[0167] The shape of these reinforcing fibers may be, for example, a cloth shape such as a roving cloth; a mat shape such as a chopped strand mat, a preformable mat, a continuous strand mat, or a surfacing mat; a strand shape such as a chopped strand; a roving shape; a nonwoven fabric shape; or a paper shape, and preferably a roving shape.
[0168] Of these reinforcing fibers, glass roving is preferable.
[0169] The fiber length of the reinforcing fibers is 10 mm or more, preferably 20 mm or more, and 60 mm or less, preferably 30 mm or less.
[0170] When the fiber length of the reinforcing fibers is equal to or greater than the above lower limit, it is possible to obtain a molded article (described later) that is excellent in strength and elastic modulus, and that is excellent in strength and rigidity even if it is thin.
[0171] On the other hand, if the fiber length of the reinforcing fibers is less than the above lower limit, the mechanical properties of the material are significantly reduced, and if the molded product (described later) is thin, sufficient strength and rigidity cannot be obtained. In addition, in terms of moldability, leakage from the periphery of the mold (amount of flash) increases, and the occurrence of demolding cracks due to the adhesion of flash to the mold becomes noticeable.
[0172] Furthermore, if the fiber length of the reinforcing fibers is equal to or less than the above upper limit, the mutual interference of the reinforcing fibers is alleviated, and the resin composition and the fibers are maintained in a uniformly dispersed state during flow even in the molding of a thin plate.
[0173] On the other hand, if the fiber length of the reinforcing fibers exceeds the above upper limit, the resin composition and the fibers separate during flow in thin plate molding, causing warping and poor filling due to uneven distribution of the fibers.
[0174] In addition, in a typical method for producing a sheet molding compound, the fiber length is determined by the cutter pitch of a rotary cutter that continuously cuts the fibers.
[0175] The aspect ratio of the reinforcing fibers (the length of the reinforcing fibers divided by the diameter of a single fiber) is, for example, 100 or more, preferably 200 or more, more preferably 500 or more, and for example, 1,000 or less.
[0176] When the aspect ratio of the reinforcing fibers is equal to or greater than the above lower limit, a high reinforcing effect of the reinforcing fibers is obtained, and the molded product has excellent mechanical properties.
[0177] Furthermore, if the aspect ratio of the reinforcing fibers is equal to or less than the upper limit, the rigidity of each reinforcing fiber is maintained, no sharp bending of the fibers occurs during flow in thin plate molding, and the molded product has excellent mechanical properties.
[0178] The thin plate molding material is obtained by blending reinforcing fibers with a resin composition.
[0179] Specifically, the thin plate molding material is obtained, for example, in the form of a sheet by impregnating reinforcing fibers with a resin composition.
[0180] Methods for preparing the thin plate molding material include known methods such as SMC (sheet molding compound), TMC (thick molding compound), BMC (bulk molding compound), etc., with SMC being preferred.
[0181] The content of the reinforcing fibers is 21% by volume or more, preferably 23% by volume or more and 28% by volume or less, based on the thin plate molding material.
[0182] The mass proportion of the reinforcing fibers in the thin plate molding material is, for example, 30 mass % or more, preferably 40 mass % or more, more preferably 45 mass % or more, and for example, 50 mass % or less.
[0183] This results in a thin plate molding material containing the resin composition and the reinforcing fibers.
[0184] In the thin plate molding material, the blending ratio of the resin component (in other words, the total amount of the double bond-containing curable polymer, the polymerizable monomer, and the shrinkage reducing agent that is blended as necessary, and the additives that are blended as necessary) is 49 volume % or more and 56 volume % or less.
[0185] That is, in the thin plate molding material, the content ratio of the reinforcing fibers is the above-mentioned predetermined ratio, and the blending ratio of the resin component is the above-mentioned predetermined ratio.
[0186] When the content ratio of the reinforcing fibers is the above-mentioned predetermined ratio and the blending ratio of the resin component is the above-mentioned predetermined ratio, the flowability of the thin plate molding material is good, and it is possible to mold a molded product that has excellent moldability (thin plate moldability) for a mold that requires a thin plate, and has excellent specific strength and specific rigidity that provide the strength and rigidity of a part even in a thin plate. This makes it possible to reduce the weight of the molded product.
[0187] On the other hand, even if the blending ratio of the resin components is the specified ratio described above, if the content ratio of the reinforcing fibers is less than the lower limit described above, the strength (specific strength) and rigidity (specific rigidity) required for the molded product will be insufficient when obtaining a thin molded product, and the strength will also be insufficient when demolded from the molding process, which is performed at high temperatures, making the product more likely to crack when demolded.
[0188] Furthermore, even if the blending ratio of the resin component is the specified ratio described above, if the content ratio of the reinforcing fibers exceeds the upper limit described above, when a molded product is obtained as a thin plate, the fluidity of the thin plate molding material as a whole will be insufficient, and some of the ends of the molded product will be resin-rich because the reinforcing fibers do not reach them, and cracks will be more likely to occur during demolding.
[0189] Furthermore, even if the content ratio of the reinforcing fibers is the specified ratio described above, if the blending ratio of the resin component is less than the lower limit described above, when obtaining a molded product (described later) as a thin plate, the fluidity of the thin plate molding material will be insufficient, and short circuits will occur in some places.
[0190] Furthermore, even if the content ratio of the reinforcing fibers is the specified ratio described above, if the blending ratio of the resin component exceeds the upper limit described above, when a molded product is obtained as a thin plate, the apparent fluidity of the thin plate molding material is good, but there will be a lot of burrs at the ends of the molded product due to the outflow of the resin composition, and the strong orientation of the reinforcing fibers in the same areas will make it more likely to develop demolding cracks.
[0191] Next, such a thin plate molding material is aged, for example, at 20° C. to 50° C. for 8 hours to 120 hours to thicken the material so that it can be subjected to hot compression molding (described later).
[0192] As a result, the sheet molding material is maintained in a shape, for example, a sheet shape. That is, the sheet molding material has a sheet shape.
[0193] Such a thin plate molding material includes a resin composition containing a resin component and a filler, and reinforcing fibers having a predetermined fiber length, the content ratio of the reinforcing fibers is a predetermined ratio, and the blending ratio of the resin component is a predetermined ratio.
[0194] Therefore, it is possible to form a molded product having excellent thin plate formability, strength and rigidity.
[0195] The molded product can be obtained by subjecting the above-mentioned thin plate molding material to heat compression molding by a known method.
[0196] The conditions for the hot compression molding are appropriately set depending on the purpose and application. Specifically, the molding temperature is, for example, 100°C or more, preferably 120°C or more, and, for example, 200°C or less, preferably 160°C or less; and the molding pressure is, for example, 1 MPa or more, preferably 3 MPa or more, more preferably 5 MPa or more, and, for example, 30 MPa or less, preferably 15 MPa or less.
[0197] This causes the thin plate molding material to harden and be molded.
[0198] This results in a molded article containing a cured product of the thin plate molding material.
[0199] The molded article has a thickness of, for example, 1.5 mm or less, preferably 1.3 mm or less, and for example, 0.8 mm or more.
[0200] If the thickness of the molded article is equal to or less than the above upper limit, the weight can be reduced.
[0201] Because the molded product contains the hardened product of the above-mentioned thin plate molding material, even if it is thin (for example, even if the thickness of the molded product is 1.5 mm or less), it is a lightweight part with excellent strength (specific strength) and rigidity (specific rigidity).
[0202] Specifically, the specific strength and specific rigidity, which take density into consideration in relation to mechanical properties such as strength and elastic modulus, are evaluated as material properties that contribute to weight reduction. In the case of using resin to reduce the weight of automobiles, the specific strength at 80°C, calculated from the bending strength (based on JIS K7074 (1988)) of a molded product in an 80°C environment, taking into consideration the deterioration of resin properties when heated, the bending modulus (based on JIS K7074 (1988)), and the density, is, for example, 130 MPa / (g / cm 3 ) or more, preferably 140 MPa / (g / cm 3 ) or more, more preferably 150 MPa / (g / cm 3 )That's all.
[0203] Similarly, the specific rigidity of the molded product at 80°C is, for example, 13 (MPa). 1 / 3 / (g / cm 3 ) or more, preferably 14.5 (MPa) 1 / 3 / (g / cm 3 ) or more, more preferably 16.0 (MPa) 1 / 3 / (g / cm 3 )That's all.
[0204] The method for measuring the specific strength and specific rigidity will be described in detail in the examples described later.
[0205] In order to obtain the above-mentioned excellent specific strength and specific rigidity, the density of the molded product is, for example, 0.8 g / mL or more, preferably 1.2 g / mL or more, more preferably 1.5 g / mL or more, and for example, 2.3 g / mL or less, preferably 1.8 g / mL or less.
[0206] The method for measuring the density will be described in detail in the Examples below.
[0207] Such molded products can be used in a wide range of applications, including building materials, housings, casting materials, machine parts, electronic and electrical parts, and various components for vehicles, ships, and aircraft.
[0208] In particular, such molded products have excellent strength (specific strength) and rigidity (specific rigidity) even when they are thin (for example, the thickness of the molded product is 1.5 mm or less), and can achieve lightweight construction, making them suitable for use in automobile parts with relatively complex shapes, such as door stiffeners. EXAMPLES
[0209] Specific numerical values of the blending ratio (content ratio), physical property values, parameters, etc. used in the following description can be replaced with the upper limit values (numerical values defined as "not more than" or "less than") or lower limit values (numerical values defined as "not less than" or "exceeding") of the corresponding blending ratio (content ratio), physical property values, parameters, etc. described in the above "Form for carrying out the invention." In addition, unless otherwise specified in the following description, "parts" and "%" are based on mass. 1.Details of ingredients Heavy calcium carbonate: second filler, average particle size d 50 5μm Glass balloon: first filler, average particle size d 50 25μm Milled carbon fiber: 1st filler, length-weighted average fiber length 200μm Glass fiber 1: Glass roving with a single fiber diameter of 12 to 14 μm cut to a fiber length of 25.4 mm, aspect ratio of about 2100 to 1800 Glass fiber 2: Glass roving with a single fiber diameter of 12 to 14 μm cut to a fiber length of 6.4 mm, aspect ratio of about 530 to 460 Carbon fiber: Regular tow of carbon fiber with a single fiber diameter of 5 to 7 μm cut to a fiber length of 25.4 mm, aspect ratio of about 5080 to 3600, product name "T700SC-12000", manufactured by Toray Industries, Inc. 2. Preparation of Unsaturated Polyester Resin Synthesis Example 1 In a flask equipped with a thermometer, a nitrogen gas inlet tube, a reflux condenser, and a stirrer, 3.3 mol of isophthalic acid and 10.5 mol of propylene glycol were charged, and polycondensation reaction was carried out at 200°C to 210°C while stirring under a nitrogen gas atmosphere. After that, when the acid value of the reaction product became 20 mgKOH / g, it was cooled to 150°C, 6.7 mol of maleic anhydride was charged, and it was reacted again at 210°C to 220°C, and an unsaturated polyester with an acid value of 27.5 mgKOH / g and a double bond equivalent of 263 g / eq. was obtained. The acid value was measured according to JIS K6901 (2008). To 100 parts by mass of the obtained unsaturated polyester, 0.01 parts by mass of hydroquinone and 66.7 parts by mass of styrene were added as polymerization inhibitors, and these were mixed uniformly to obtain an unsaturated polyester resin with a styrene content of 40%.
[0210] Synthesis Example 2 A flask equipped with a thermometer, nitrogen gas inlet tube, reflux condenser, and stirrer was charged with 10.0 mol of maleic anhydride, 6.5 mol of propylene glycol, and 4.0 mol of neopentyl glycol, and the mixture was subjected to a polycondensation reaction at 200°C to 210°C while stirring under a nitrogen gas atmosphere, to obtain an unsaturated polyester with an acid value of 26.5 mgKOH / g and a double bond equivalent of 171 g / eq. To 100 parts by mass of the obtained unsaturated polyester, 0.01 parts by mass of hydroquinone and 66.7 parts by mass of styrene were added as polymerization inhibitors, and these were mixed uniformly to obtain an unsaturated polyester resin with a styrene content of 40%.
[0211] Synthesis Example 3 In a flask equipped with a thermometer, a nitrogen gas inlet tube, a reflux condenser, and a stirrer, 5.0 mol of isophthalic acid, 6.5 mol of propylene glycol, and 4.0 mol of neopentyl glycol were charged, and polycondensation reaction was carried out at 200°C to 210°C while stirring under a nitrogen gas atmosphere. After that, when the acid value of the reaction product became 20 mgKOH / g, it was cooled to 150°C, 5.0 mol of maleic anhydride was charged, and the reaction was carried out again at 210°C to 220°C, to obtain an unsaturated polyester with an acid value of 27.0 mgKOH / g and a double bond equivalent of 392 g / eq. To 100 parts by mass of the obtained unsaturated polyester, 0.01 parts by mass of hydroquinone and 66.7 parts by mass of styrene were added as polymerization inhibitors, and these were mixed uniformly to obtain an unsaturated polyester resin with a styrene content of 40%. 3. Preparation of Vinyl Ester Resin Synthesis Example 4 In a reaction vessel (flask) equipped with a stirrer, reflux condenser, and gas inlet tube, 1850 parts by mass (10.0 equivalents) of bisphenol A type epoxy resin (epoxy equivalent 185), 317 parts by mass (2.78 equivalents) of bisphenol A, and 0.5 parts by mass of triethylbenzylammonium chloride as a catalyst were charged, and while blowing in nitrogen, the mixture was reacted at 150°C for 5 hours to obtain an epoxy resin with an epoxy equivalent of 298. After cooling to 120°C, 2.0 parts by mass of hydroquinone as a polymerization inhibitor, 2.0 parts by mass of triethylbenzylammonium chloride as a catalyst, and 636 parts by mass (7.40 equivalents) of methacrylic acid were added, and while blowing in air, the mixture was reacted at 110°C for 8 hours to obtain a vinyl ester with an acid value of 8.0 mgKOH / g and a double bond equivalent of 379 g / eq. Next, 1869 parts by mass of styrene was added to this vinyl ester to obtain a vinyl ester resin with a styrene content of 40% by mass. 4. Manufacturing of sheet metal molding materials Example 1, Example 2, Reference Example 3, Example 4 to Example 1 2. Reference example 13. Comparative Examples 1 to 6 (Preparation of thin sheet molding material) According to the formulations in Tables 1 and 2, each component except the thickener was mixed uniformly to obtain a resin composition. The thickener was added to the obtained resin composition (paste), and the mixture was stirred for 3 minutes, and then immediately fed to an SMC impregnating machine (Tsukishima Kikai Co., Ltd.), where reinforcing fibers were added and thoroughly impregnated. The mixture was then aged for 48 hours to obtain a sheet-shaped thin plate molding material having a thickness of 2 mm.
[0212] As described in the synthesis examples, 60 parts by mass of the double bond-containing curable polymer and 40 parts by mass of the polymerizable monomer were mixed in advance and used for the preparation, and 40 parts by mass of polyvinyl acetate and polystyrene were mixed in advance and 60 parts by mass of the polymerizable monomer were used for the preparation. (Preparation of molded products for measuring mold shrinkage, density, and 80°C bending properties) From the above thin plate molding material, a thin plate molding material measuring 140 mm in length and 140 mm in width was cut out, and three of these were stacked together. Using a 100-ton press for FRP molding and a positive mold for SMC molding with a cavity shape of a flat plate measuring 300 mm in length and 300 mm in width heated to 140°C, the stacked thin plate molding material was placed in the center of the plate, and it was heated and pressurized for 5 minutes under a molding pressure of 10 MPa.
[0213] This resulted in a molded product measuring 300 x 300 mm and with a thickness of 1.3 mm. 5. Evaluation (double bond equivalent) For the unsaturated polyesters of Synthesis Examples 1 to 3, the double bond equivalent was calculated as the amount of unsaturated polyester (the value obtained by subtracting the amount of dehydration from the sum of <molecular weight of polybasic acid × number of moles> and <molecular weight of polyhydric alcohol × number of moles>) divided by the number of moles of the ethylenically unsaturated bond-containing polybasic acid.
[0214] For the vinyl ester of Synthesis Example 4, the double bond equivalent was calculated as the value obtained by dividing the total amount of the main raw materials used in the synthesis by the number of moles of methacrylic acid.
[0215] The results are shown in Tables 3 and 4. (density) The density of the molded products (thickness 1.3 mm) of each of the Examples and Comparative Examples was determined by Archimedes' method using water at 25° C. The results are shown in Tables 3 and 4. (Mold shrinkage rate) For the molded products (thickness 1.3 mm) of each Example and Comparative Example, the mold shrinkage was measured in accordance with JIS K6911 (1995) except for using the dimensions of the mold and molded product used in molding. The results are shown in Tables 3 and 4. (Flexural strength and flexural modulus) Rectangular test pieces were cut out by machining from the molded products (thickness 1.3 mm) of each Example and Comparative Example, and a bending test was carried out in an 80°C environment in accordance with JIS K7017 (1999) Method A Class II (plate thickness was 1.3 mm) to measure bending strength and bending modulus. The results are shown in Tables 3 and 4. (specific strength) For the molded articles (thickness 1.3 mm) of each Example and Comparative Example, the 80° C. specific strength was calculated from the measurement results of 80° C. bending strength and density according to the following formula (3).
[0216] Specific strength at 80°C = (flexural strength at 80°C) / (density) (3) The specific strength at 80°C was evaluated according to the following criteria. The results are shown in Tables 3 and 4. ◎: Specific strength at 80℃ is 150MPa / (g / cm 3 ) and above. 〇: 80℃ specific strength is 140MPa / (g / cm 3 ) or more 150MPa / (g / cm 3 ) or less. △: 80℃ specific strength is 130MPa / (g / cm 3 ) or more 140MPa / (g / cm 3 ) or less. ×: 80℃ specific strength is 130MPa / (g / cm 3 ) or less. (specific stiffness) For the molded articles (thickness 1.3 mm) of each Example and Comparative Example, the 80° C. specific rigidity was calculated from the measurement results of the 80° C. flexural modulus and density according to the following formula (4).
[0217] Specific stiffness = (Flexural modulus) 1 / 3 / (density)(4) The specific rigidity at 80°C was evaluated according to the following criteria. The results are shown in Tables 3 and 4. ◎: Specific rigidity at 80℃ is 16.0(MPa) 1 / 3 / (g / cm 3 ) and above. ○: 80℃ specific rigidity is 14.5(MPa) 1 / 3 / (g / cm 3 ) or more than 16.0 (MPa) 1 / 3 / (g / cm 3 ) or less. △: Specific rigidity at 80℃ is 13.0(MPa) 1 / 3 / (g / cm 3 ) or more than 14.5 (MPa) 1 / 3 / (g / cm 3 ) or less. ×: 80℃ specific rigidity is 13.0(MPa) 1 / 3 / (g / cm 3 ) or less. (Thin plate formability) The formability of the thin plate was evaluated using a mold with a flat surface of 300 x 600 mm and vertical surfaces around the periphery, by the amount of leakage (amount of flash) from the periphery of the mold during molding, the state of filling the entire mold cavity, and cracks when demolded. The equipment and molding conditions used for the evaluation are shown below.
[0218] Mold: A steam-heatable positive mold for SMC molding with a rectangular flat surface of 300 x 600 mm and a vertical surface of 2 mm thickness and 25 mm height around the flat surface, a clearance of 100 to 200 μm, and a shear edge with a travel of 20 mm. Press: 500-ton FRP molding press manufactured by Kawasaki Hydro Engineering Co., Ltd. Evaluation of sheet metal formability for a molded product with a thickness of 1.3 mm Molding conditions: mold temperature 145°C on the cavity side, 135°C on the core side, two sheets of thin sheet molding material cut to 200 x 400 mm were placed in the center of the 300 x 600 mm flat surface of the mold, and heating and pressure were applied for 3 minutes under the following conditions: final press closing speed 0.5 mm / sec, press output 180 tons (molding pressure approximately 10 MPa).
[0219] Evaluation of sheet metal formability for a molded product with a thickness of 2.2 mm Molding conditions: The evaluation was carried out under the same conditions as for the evaluation of sheet metal formability for a molded product with a thickness of 1.3 mm, except that three sheets of sheet metal molding material cut to 200 x 400 mm were stacked and placed in the center of the flat surface of the mold with dimensions of 300 x 600 mm.
[0220] <Amount of burrs> The amount of flash (volume) during molding was measured for the molded products (thickness 1.3 mm) and molded products (thickness 2.2 mm) of each of the Examples and Comparative Examples.
[0221] Specifically, the burrs on the share edge of the molded products of each Example and Comparative Example were cut off with a knife, and the amount of burrs (volume) was calculated using the weight and the density of each Example and Comparative Example.
[0222] The amount of burrs was evaluated according to the following criteria. The results are shown in Tables 3 and 4. 〇: Burr amount is 3.6cm 3 It was less than. △: Burr amount is 3.6cm 3 Over 7.2cm 3 It was less than. ×: Burr amount is 7.2cm 3 That was all.
[0223] <Filling state> The filling state during molding was visually observed for the molded products (thickness 1.3 mm) and molded products (thickness 2.2 mm) of each Example and Comparative Example. The filling state was evaluated according to the following criteria. The results are shown in Tables 3 and 4. Good: All components of the sheet molding material are filled to the ends of the molded product. Resin-rich: There were no unfilled areas, but areas containing only the resin composition and no or very little reinforcing fibers were observed. Short: A portion where neither the resin composition nor the reinforcing fibers existed (unfilled portion) was observed.
[0224] <Number of demold cracks> When the molded products (thickness 1.3 mm) and molded products (thickness 2.2 mm) of each Example and Comparative Example were demolded to check the filling state, the occurrence of cracks was observed. 10 molds were molded, and the number of pieces that had cracks when demolded was counted.
[0225] The number of cracks upon demolding was evaluated according to the following criteria. The results are shown in Tables 3 and 4. ○: The number of units with cracks was between 0 and 1. △: The number of units with cracks was 2 to 4. ×: The number of cracks was 5 or more. 6. Discussion Example 1 , Example 2, Reference Example 3, Example 4 Example 1 2. Reference example Regarding No. 13, the content of reinforcing fibers is 21 vol% or more and 28 vol% or less, and the blending ratio of the resin component is 49 vol% or more and 56 vol% or less.
[0226] On the other hand, in Comparative Example 1, the content of reinforcing fibers is less than 21% by volume.
[0227] In Comparative Example 2, the content of reinforcing fibers exceeds 28 volume %.
[0228] In Comparative Example 3, the blending ratio of the resin component is less than 49% by volume.
[0229] In Comparative Example 4, the blending ratio of the resin component exceeds 56% by volume.
[0230] In Comparative Example 6, the content of reinforcing fibers is less than 21% by volume, and the blending ratio of the resin component is less than 49% by volume.
[0231] Example 1, Example 2, Reference Example 3, Example 4 to Example 1 2. Reference example No. 13 has excellent sheet formability in the case of a molded product having a complex shape and a large thickness (specifically, a molded product (thickness 2.2 mm)) as used in the evaluation of sheet formability, and is also excellent in Example 1, Example 2, Reference Example 3, Example 4 to Example 1. 2. Reference exampleIt can be seen that No. 13 has excellent thin plate formability even when the molded product is thin (specifically, when the molded product is 1.3 mm thick).
[0232] On the other hand, it is understood that the thin plate formability is deteriorated when the molded product has a complex shape and a thin thickness as used in the thin plate formability evaluation in Comparative Examples 1 to 4 and 6. Therefore, it is understood that it is difficult to stably perform mass production molding in a molded product with a more complex shape than the one used in this evaluation (many actual parts generally have parts that are difficult to fill due to their design).
[0233] From this, it can be seen that if the content ratio of the reinforcing fibers and the blending ratio of the resin component are set to the above-mentioned predetermined ratios, the moldability (thin plate moldability) in a mold for a desired thin plate is excellent.
[0234] In addition, Example 1, Example 2, Reference Example 3, Example 4 to Example 1 2. Reference example 13, it can be seen that the strength (specific strength) and rigidity (specific rigidity) are also high.
[0235] From the above, it can be seen that if the content ratio of reinforcing fibers and the blending ratio of resin components are set to the above-mentioned specified ratios, the sheet will have excellent formability (sheet formability) for a mold for which a thin sheet is desired, as well as excellent strength (specific strength) and rigidity (specific rigidity).
[0236] [Table 1]
[0237] [Table 2]
[0238] [Table 3]
[0239] [Table 4]
[0240] The above invention is provided as an exemplary embodiment of the present invention, but this is merely an example and should not be interpreted as being limited. Modifications of the present invention that are obvious to those skilled in the art are included in the scope of the following claims. [Industrial Applicability]
[0241] The thin plate molding material and molded product of the present invention can be suitably used in various members of building materials, housings, casting materials, machine parts, electronic and electric parts, vehicles, ships, aircraft, etc.
Claims
1. The present invention includes a resin composition including a resin component and a filler, and reinforcing fibers having a fiber length of 10 mm or more and 60 mm or less, The content of the reinforcing fibers is 21% by volume or more and 28% by volume or less, The blending ratio of the resin component is 49% by volume or more and 56% by volume or less, The resin component includes a double bond-containing curable polymer, a polymerizable monomer, and a shrinkage reducing agent, The double bond-containing curable polymer comprises an unsaturated polyester or vinyl ester; The polymerizable monomer comprises styrene, the blending ratio of the polymerizable monomer is 20 parts by mass or more and 60 parts by mass or less with respect to 100 parts by mass of the total amount of the double bond-containing curable polymer, the polymerizable monomer, and the low shrinkage agent, the blending ratio of the filler is 30 parts by mass or more and 150 parts by mass or less with respect to 100 parts by mass of the total amount of the double bond-containing curable polymer, the polymerizable monomer, and the low shrinkage agent, A thin plate molding material, characterized in that the reinforcing fibers are made of glass fibers.
2. The thin plate molding material according to claim 1, wherein the aspect ratio of the reinforcing fibers is 500 or more.
3. 2. The thin plate molding material according to claim 1, wherein the filling material contains a filler having an average maximum length of 15 μm or more and 300 μm or less.
4. 4. The thin plate molding material according to claim 3, wherein the filler is a hollow glass having an average maximum length of 15 μm or more and 50 μm or less.
5. 4. The thin plate molding material according to claim 3, wherein the filler is milled carbon fiber having an average maximum length of 100 μm or more and 300 μm or less.
6. 2. The thin plate molding material according to claim 1, wherein the double bond equivalent of the double bond-containing curable polymer is 200 g / eq. or more and 350 g / eq. or less.
7. A cured product of the thin plate molding material according to claim 1, A molded article having a thickness of 1.5 mm or less.
Citation Information
Patent Citations
Styrenic resin composition having resistance to chlorofluorocarbon
JP1994240076A
Molding material and molded article
JP2009029921A
Prepreg
JP2017141314A
Molding material and molding thereof
JP2019137774A
Carbon fiber sheet material, compact, method for producing carbon fiber sheet material and method for producing compact
JP2020133048A